2020
DOI: 10.1167/tvst.9.2.29
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Generative Adversarial Networks Model for Synthetic Optical Coherence Tomography Images of Retinal Disorders

Abstract: Purpose To assess whether a generative adversarial network (GAN) could synthesize realistic optical coherence tomography (OCT) images that satisfactorily serve as the educational images for retinal specialists, and the training datasets for the classification of various retinal disorders using deep learning (DL). Methods The GANs architecture was adopted to synthesize high-resolution OCT images trained on a publicly available OCT dataset, including urgent referrals (37,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…In our previous study, we reported that GANs were able to synthesize realistic high-resolution OCT images and achieve a high AUC of 0.98 for screening urgent referable retinal diseases, such as choroidal neovascularization or diabetic macular edema. 13 In the current study, our DL model that trained on synthetic OCT images achieved a similar AUC of 0.94, which was comparable with that of DL models trained in all-real OCT images, such as those reported by Xu et al 5 (4036 AS-OCT images) and Fu et al 7 (8270 AS-OCT ACA images). As different reference standards were used, our study cannot be directly compared to those of Xu et al and Fu et al It should be noted that a small validation dataset makes it challenging to interpret a small difference in model performance, and the distribution of open- and closed-angle images was not the same in the two training datasets, which could also introduce training bias.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our previous study, we reported that GANs were able to synthesize realistic high-resolution OCT images and achieve a high AUC of 0.98 for screening urgent referable retinal diseases, such as choroidal neovascularization or diabetic macular edema. 13 In the current study, our DL model that trained on synthetic OCT images achieved a similar AUC of 0.94, which was comparable with that of DL models trained in all-real OCT images, such as those reported by Xu et al 5 (4036 AS-OCT images) and Fu et al 7 (8270 AS-OCT ACA images). As different reference standards were used, our study cannot be directly compared to those of Xu et al and Fu et al It should be noted that a small validation dataset makes it challenging to interpret a small difference in model performance, and the distribution of open- and closed-angle images was not the same in the two training datasets, which could also introduce training bias.…”
Section: Discussionsupporting
confidence: 87%
“…In a previous study, we proposed a GAN approach to generate realistic OCT images to serve as training datasets for DL algorithms and education images for retinal specialists. 13 We showed that DL algorithms trained with only generated images achieved performance nearly comparable to the results obtained from training on real images. In the present work, we first demonstrate that a similar technique can also generate realistic AS-OCT images.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…First, our semi-supervised GANs architecture can only synthesize images with 128×128 pixels lower than the Casia AS-OCT images' resolution. Our previous study reported a progressively grown GANs architecture to generate realistic OCT images with higher resolutions (e.g., 256×256 or above) (41). Second, we only used two independent testing datasets with small sample sizes, making the little difference in model performance challenging to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…9,[19][20][21][22][23][24][25][26] Since ophthalmology has been at the forefront of the DL revolution, there are numerous potential applications of synthetic images, starting with fundus 9,19,20 and optical coherence tomography (OCT). [27][28][29] Synthetic images can be modified to adjust image features such as pigmentation, 9 image quality, 30 and even disease severity. 31 One of many potential applications is as an alternative solution to increase the size and diversity of training datasets for DL algorithms.…”
Section: Introductionmentioning
confidence: 99%